Comparison of atrio-femoral and femoro-atrial venovenous extracorporeal membrane oxygenation in adult. (January 2022) - Ling, Steven Kin-ho
Introduction: Different cannulation approaches existed for veno-venous extracorporeal membrane oxygenation (VV ECMO). We aimed to compare the atrio-femoral (AF) and femoro-atrial (FA) configuration in terms of their flow efficiency and influence on patient outcome. Method: This was a single-centre, retrospective case control study. Adult patients admitted to the Intensive Care Unit and required VV ECMO service at Tuen Mun Hospital, Hong Kong, from June 2015 to January 2020 were included. Data were collected from our ECMO database for comparison. Results: Between June 2015 and January 2020, eight patients received AF configuration and 19 patients received FA configuration. The maximum achieved flow in the AF group was significantly higher than that in the FA group (4.08 ± 0.57 L/min vs. 3.52 ± 0.58 L/min, p = 0.03). The fluid balance in first 3 days of ECMO was significantly lower in the AF group compared to that in the FA group (1.16 ± 2.71 L vs. 3.46 ± 1.97 L, p = 0.02). As well, the chance for successful awake ECMO was statistically higher in the AF group (p = 0.048). Conclusion: Atrio-femoral configuration in VV ECMO was associated with a higher maximum achieved ECMO flow, less fluid gain in first 3 days of ECMO and more successful awake ECMO.